Talent tectonics : navigating global workforce shifts, building resilient organizations, and reimagining the employee experience - Hunt, Steven T., 1965- (John Wiley & Sons, Inc., 2022)
"Talent Tectonics is written to help leaders create resilient workforces and organizations that will thrive in a fast-changing world with increasing shortages of skilled labor. It is based on engagements with hundreds of organizations around the world combined with research from industrial-organizational psychology, management science, socioeconomics, and related fields. It is a product of the author's unique experience working at the intersection of people, technology, and work. The phrase 'talent tectonics' refers to fundamental shifts reshaping work and organizations. The two biggest being the accelerating pace of change caused by digitalization and the reshaping of labor markets caused by declining birth rates and increasing lifespans around the world. These deep structural changes create visible changes in the nature of organizations and work. Similar to how movement of underlying geological tectonic plates drive changes on the surface of the earth. Most of the changes to work caused by talent tectonics are not initiated by companies. They are an inevitable consequence of larger social and economic forces. Companies can treat these shifts as threats to be managed or opportunities to be leveraged, but either way they must react to survive. Talent tectonics cannot be ignored or avoided. Companies must adapt or suffer the consequences. This book explains how talent tectonics are changing work. But also addresses one thing about work that is not changing: how people are influenced by their work experiences. Despite popular assertions that generations are radically different from one another, the fundamental psychology of people changes very little over time. The kinds of work experiences that make us happy, support our development, and motivate us are relatively constant from one generation to the next. What does change is the impact work experiences have on company performance and employee's ability to get the work experiences they want. Creating positive employee experiences is critical for attracting and retaining talent in an increasingly competitive labor market. It is also necessary for tapping into people's innate capacities for learning, adapting, collaborating, and creating. These skills are at the heart of having an agile, high performing organization. Achieving this requires understanding how the psychology of people interacts with the experience of work to impact adaptability, wellbeing, and performance. Balancing company needs with employee experience to create supportive, inclusive, healthy, agile, and productive organizations. The book discusses how companies can do this by rethinking approaches to job design, staffing, development, management, compensation, and organizational culture. Readers will leave this book with a better understanding of how and why work is changing, and tactical tips and frameworks to redesign their workforce management methods to leverage the power of employee experience to create more successful companies."--